Virtual Community Engagement Studio (V-CES): Engaging Mothers With Mental Health and Substance Use Conditions in Research - Zisman-Ilani, Yaara; Buell, Jennifer; Mazel, Shayna; Hennig, Shannon; Nicholson, Joanne (Frontiers in Psychiatry, 2022)
Active engagement of community stakeholders is increasingly encouraged in behavioral health research, often described as a co-production approach. Community stakeholders (e.g., patients, providers, policy makers, advocates) play a leading role together with research investigators in conducting the various phases of research, including conceptualization, design, implementation, and the interpretation and dissemination of findings. The concept of co-production has promising benefits for both the target population and the research outcomes, such as producing person-centered interventions with greater acceptability and usability potential. However, it is often the case that neither researchers nor community members are trained or skilled in co-production methods. The field of behavioral health research lacks tools and methods to guide and promote the engagement of diverse stakeholders in the research process. The purpose of this methods paper is to describe the Virtual Community Engagement Studio (V-CES) as a new method for engaging vulnerable populations like mothers with mental health and substance use conditions in research. We piloted the method in collaboration with the Maternal Mental Health Research Collaborative (MMHRC), focusing on one of the most vulnerable, under-researched populations, mothers coping with maternal mental health and/or substance abuse disorders. Our pilot included mothers and providers who work with them as Community Experts to inform all phases of research design and implementation, and the interpretation and application of findings. The aim of this article is to describe the V-CES as a powerful tool that supports the engagement of mothers with mental health and/or substance use disorders and other community stakeholders in research, to provide examples of its use, and to make recommendations for future use, based on lessons learned. The V-CES toolkit is available for use with this target population as well as others.